Os municípios no contexto da federação brasileira - Breda, Jean Carlos (My University, 2025)
The municipalities are a fundamental part of the federative pact, being the place where the main demands of society take place. Small municipal structures are essential in the Brazilian context, since they organize their territory and the needs of their communities in a centralized way. The municipality is a third level federative entity in the organization of the State and has its own attributions established by the Federal Constitution. However, many municipalities are not self-sufficient in economic and financial terms, with resources coming from the Union and the States as their main source of income. Based mainly on the economic issue, several proposals for legislation have been made aiming to modify the viability of municipalities, mainly concerning their extinction and creation. The Proposal of Amendment to the Constitution number 188/2019 came in this context, with the wording seeking to extinguish municipalities with less than five thousand inhabitants and that do not produce revenues that make up 10% of their budget. This work makes an analysis of the situation presented and analyzes the main impacts of the extinction of municipalities in the Brazilian scenario. [resumo fornecido pelo autor]
Os municípios são parte fundamental do pacto federativo, sendo o local onde as principais demandas da sociedade acontecem. As pequenas estruturas municipais se fazem essenciais no contexto brasileiro, uma vez que organizam de forma centralizada seu território e as necessidades de sua comunidade. O município é ente federativo de terceiro grau na organização do Estado e possui atribuições próprias estabelecidas pela Constituição Federal. Entretanto, muitos municípios não são autossuficientes em termos econômicos e financeiros, sendo os recursos advindos da União e Estados sua principal fonte de receitas. Com base principalmente na questão econômica, diversas propostas de legislação se fizeram presentes visando modificar as questões de viabilidade de municípios, principalmente relativos à sua extinção e criação. A Proposta de Emenda a Constituição número 188/2019 veio neste contexto, com a redação buscando extinguir municípios com menos de cinco mil habitantes e que não produzem receitas que perfaçam 10% de seu orçamento. Esse trabalho faz uma análise da situação apresentada e analisa os principais impactos da extinção dos municípios no cenário brasileiro. [resumo fornecido pelo autor]
Keywords: Direito municipal; Princípio federativo; Cidades e vilas - Criação